The Effect of Learning Management Using Inquiry-Based Learning (7E) with Flipped Classroom on Learning Achievement Politics Unit and Analytical Thinking of Grade 9 Students - Endoo, Parunya; Jongkonklang , Sirinat (Ratchaphruek Journal, 2025)
This research was to study the effect of using inquiry -based learning (7E) with flipped inquiry classroom. It aimed to: 1) Compare learning achievement before and after learning using and their learning achievement against the 70 percent criterion; 2) Compare the analytical thinking before and after learning; and 3) Study the learning characteristics using inquiry-based learning (7E) with the flipped classroom. The sample group was 38 students of grade 9 students, selected by cluster random sampling. The research instruments included lesson plans, an achievement test, analytical thinking test and the learning characteristics test. The data were statistically analyzed by percentage, mean, standard deviation and t-test. The research findings showed that: 1) Learning achievement after learning was higher than before learning and was higher than 70 percent criterion with significantly at the .05 level, 2) Analytical thinking after learning was statistically significantly higher than before learning at .05 level. and 3) Learning characteristics using inquiry-based learning (7E) with flipped classroom was at a high level.